A cross sectional study to assess the knowledge and response to dog bite among the urban and rural population of Hubballi taluk - Godbole, Maneesha; Joshi, Anjana Ramachandra; Bant, Dattatraya D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Rabies is a fatal zoonotic disease of the central nervous system, most commonly caused by the bite of rabid dogs. Globally canine rabies causes 59,000 human deaths, over 3.7 million DALYs and 8.6 billion USD economic losses annually. These losses are due to a lack of knowledge about wound management and post-exposure prophylaxis. The objective of the study was to assess the knowledge and practices following dog bite and its management among the urban and rural population. Methods: A cross-sectional study was conducted in the field practice area of KIMS, Hubli. 120 households of the urban and rural locality were interviewed with a semi-structured pretested questionnaire. Results: Overall 89.16% of the study population was aware that the disease can be prevented by vaccination. 35% of the rural and 28% of the urban population believed that the disease can spread from person to person. The knowledge about the site and the number of doses of vaccine was poor among both the population. The harmful practices for treatment of bite were still prevalent among both rural (25%) and urban (8.3%) population. Conclusions: The knowledge about the dog bite management and Rabies prevention is insufficient among both populations. There are myths and misconceptions about the disease and wound management. Practices like application of harmful substances like lime, turmeric, mud are the problems hindering rabies prevention and control. Proper steps need to be taken up to control the canine rabies.